O protagonismo da mulher na gestão e sucessão da agricultura familiar - Glesse, Jaqueline Aparecida Daronch (2022)
This dissertation investigated the role of women in management and their participation in the process of succession in family farming in the municipality of Marechal Cândido Rondon, west of the state of Paraná. The study aimed to describe the profile of rural women and diagnose their relationship with property management. It also sought to diagnose its participation in social spaces and its role in the succession process. The methodology was characterized by a case study, using field research as a technical procedure, with a qualitative and quantitative approach. Data were collected through questionnaires applied to 21 women farmers. The survey results made it possible to trace the profile of women, identify that they actively participate in productive activities, in 90.5% of the properties, productive activities are carried out together and in 61.9% of the responses women participate in decision-making. It is possible to say that rural women have a significant role in property activities and management, a fact that was evidenced when 57.1% of women responded that they were prepared to manage the rural property alone, if necessary. It was possible to evidence the female participation in associative, cooperative and union actions, where 95.2% answered to be associated with some cooperative, 100% in some association and 14.3% in the rural union. With regard to courses and training, in 57.1% of the women answered that they participate in the proposed activities, with reflexes in obtaining training, and in parallel, inserting them in the community, giving them tools in the search for the conquest of their social space, having an important role in the existential cleanliness and in the search to be part. In 47.6% of the responses, the expression of the women's desire for their children to continue the activities of the productive units, however, as caveats, as they seek to consolidate profitable units that present quality of life and financial return to those involved. Due to their maternal characteristics, no matter how perceptible the desire for their children to remain in rural areas, they are concerned with making clear the freedom to make their choices. It is important to note that in 76.2% of the responses there is no definition or indication of successors.